An evaluation of third-year student teachers' self-efficacy in English second language communicative competence - Hass, Atrimecia; Vogt, Emmanuel (Journal for Language Teaching, 2025)
The significant decline of the English language proficiency levels amongst language students have aroused concern amongst university language teachers. Although studies have been conducted on self-efficacy in second language environments, minimal research has been conducted on students' self-efficacy and their communicative competence in English as a second language. The study aims to investigate how students' self-efficacy beliefs regarding their English language proficiency impacts their communicative competence, and how this relationship differs across various language proficiency levels among education students at the Central University of Technology, Free State (CUT). This study draws from Halliday’s Systemic Functional Linguistics Theory and Hylands' (2002) discourse analysis as theoretical lenses to explore the link between language and the purposes it uses to perform in educational contexts. The study employed a quantitative research design to collect data through a survey which was distributed and collected from third-year education students majoring in English. The findings of the study indicated that there is a positive correlation between students' self-efficacy in their English language proficiency and their communicative competence. The study reveals that factors such as past language learning experiences, language anxiety, and teacher feedback can significantly impact students' self-efficacy and communicative competence.